Histoplasmose cutânea reveladora de infecção pelo HIV - Marques, Silvio Alencar [UNESP]; Camargo, Rosangela Maria Pires de [UNESP]; Silvares, Maria Regina Cavariani [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (FapUNIFESP (SciELO), 2013)
Histoplasmosis is a systemic mycosis endemic in extensive areas of the Americas. The authors report on an urban adult male patient with uncommon oral-cutaneous lesions proven to be histoplasmosis. Additional investigation revealed unnoticed HIV infection with CD4+ cell count of 7/mm3. The treatment was performed with amphotericin B, a 2065 mg total dose followed by itraconazole 200mg/daily plus antiretroviral therapy with apparent cure. Histoplasmosis is an AIDS-defining opportunistic disease process; therefore, its clinical diagnosis must drive full laboratory investigation looking for unnoted HIV-infection. © 2013 by Anais Brasileiros de Dermatologia.
Cutaneous histoplasmosis disclosing an HIV-infection
Keywords: Acquired immunodeficiency syndrome; Amphotericin B; Histoplasmosis; amphotericin B deoxycholate; antiretrovirus agent; itraconazole; adult; biopsy; case report; CD4 lymphocyte count; CD8+ T lymphocyte; histopathology; histoplasmosis; human; Human immunodeficiency virus infection; human tissue; malaise; male; mouth examination; mouth lesion; serodiagnosis; virus load